The Efficacy and Safety of Zhengqing Fengtongning for Knee Osteoarthritis: A Systematic Review and Meta-Analysis of Randomized Clinical Trials. (20th January 2022) - Huang, Zeling; Mao, Xiao; Chen, Junming; He, Junjun; Shi, Shanni; Gui, Miao; Gao, Hongjian; Hong, Zhenqiang
Abstract : Background . Zhengqing Fengtongning release tablet (ZQFTN) is a proprietary Chinese medicine preparation of sinomenine, the main active component of the traditional Chinese medicine (TCM) Sinomenium acutum . It is used in China as a complementary and alternative medicine (CAM) for knee osteoarthritis (KOA). The objective of this study was to evaluate the clinical efficacy and safety of ZQFTN in KOA treatment. Method. Randomized controlled trials of ZQFTN in KOA treatment were searched in PubMed, Cochrane Library, China National Knowledge Infrastructure, Chinese Scientific Journals Database, and Wanfang database. Two reviewers independently conducted the screening, extracted the data, and assessed the methodological quality. Statistical analysis was performed using RevMan 5.3 software. Results . Eighteen studies were assessed that included 1512 participants (757 in the treatment group and 755 in the control group). The results showed that compared with the control group, the Visual Analogue Scale (standardized mean difference (SMD) = −0.87, 95% confidence interval (CI): [−1.08, −0.66], P < 0.001 ), Western Ontario and Mc Master University (WOMAC) Osteoarthritis Index pain score (SMD = −0.67, 95% CI: [−0.88, −0.46], P < 0.001 ), WOMAC stiffness score (SMD = −0.53, 95% CI: [−0.86, −0.20], P = 0.001 ), WOMAC function score (SMD = −0.76, 95% CI: [−0.97, −0.55], P < 0.001 ), serum interleukin-1 β level (SMD = −4.36, 95% CI: [−6.41, −2.31], P < 0.001 ), and serum tumor necrosis factor- α level (SMD = −8.45, 95% CI: [−11.20, −5.69], P < 0.001 ) of the ZQFTN treatment group were lower, and the total effective rate was higher relative risk ( RR = 1.15, 95% CI [1.07, 1.23], P < 0.001 ). There was no significant difference in the incidence of adverse reactions between the two groups ( RR = 0.96, 95% CI: [0.69, 1.35], P = 0.82 ). Conclusion . ZQFTN can effectively relieve knee pain, morning stiffness, and daily activity function disorders, reduce the expression of inflammatory factors in serum, and improve the total clinical response rate without increasing the incidence of adverse reactions. Therefore, ZQFTN has considerable potential as a CAM for KOA. However, due to the limitation of the quality of the included studies, the strength of this conclusion is affected. In the next step, multicenter, large sample, high-quality randomized controlled studies are needed to further confirm the present conclusion.